Notifiche
Cancella tutti

!!!

  

0
image
Autore
Etichette discussione
1 Risposta



3

Foto dritta!!

image

1 - (2 + √2 - x)/(2 + √2) = (x - 2 + √2)/(2 - √2)

moltiplico per (2 + √2)·(2 - √2) = 2

2 - (2 + √2 - x)·(2 - √2) = (x - 2 + √2)·(2 + √2)

x·(2 - √2) = x·(√2 + 2) - 2

x·(√2 + 2) - x·(2 - √2) = 2

2·√2·x = 2---> x = √2/2 dm = diagonale maggiore

1/3·(√2/2) = √2/6 dm = diagonale minore

calcolo lato con Th Pitagora attraverso le semidiagonali:

l = √((√2/4)^2 + (√2/12)^2)---> l = √(1/8 + 1/72) = √5/6 dm

2·p = 4·(√5/6) = 2·√5/3 dm

Α = 1/2·(√2/2)·(√2/6) = 1/12 dm^2

 

 



Risposta
SOS Matematica

4.6
SCARICA